Fbw7 and its counteracting forces in stem cells and cancer: Oncoproteins in the balance. (February 2016) - Cremona, Catherine A.; Sancho, Rocio; Diefenbacher, Markus E.; Behrens, Axel
Abstract: Fbw7 is well characterised as a stem cell regulator and tumour suppressor, powerfully positioned to control proliferation, differentiation and apoptosis by targeting key transcription factors for ubiquitination and destruction. Evidence in support of these roles continues to accumulate from in vitro studies, mouse models and human patient data. Here we summarise the latest of these findings, highlighting the tumour-suppressive role of Fbw7 in multiple tissues, and the rare circumstances where Fbw7 activity can be oncogenic. We discuss mechanisms that regulate ubiquitination by Fbw7, including ubiquitin-specific proteases such as USP28 that counteract Fbw7 activity and thereby stabilise oncoproteins. Deubiquitination of key Fbw7 substrates to prevent their destruction is beginning to be appreciated as an important pro-tumourigenic mechanism. As the ubiquitin-proteasome system represents a largely untapped field for drug development, the interplay between Fbw7 and its counterpart deubiquitinating enzymes in tumours is likely to attract increasing interest and influence future treatment strategies.